Edukasi Sekolah Ramah Lingkungan dan Kewirausahaan Melalui Pembuatan SILERY (Sabun Cuci Lerak Ecofriendly) di SMP Negeri 16 Malang - Mokhamad Husni Mubaroq; Laila Citra; Lidiyatul Muna; Nurul Ratnawati (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The widespread use of chemical-based soaps has had a negative impact on the environment and human health. The hazardous chemicals contained in conventional cleaning products can pollute the air, damage ecosystems, and trigger skin and other health problems. This problem has become a concern in interest-based education, which emphasizes the importance of developing environmental awareness from an early age. In response to this issue, a community service activity was carried out at SMP Negeri 16 Malang by the Student Leadership Project Team of the Pre-Service PPG, State University of Malang. This activity aimed to raise ecological awareness and entrepreneurial spirit in students through a workshop on making natural soap from soap nuts, named "SILERY" (Environmentally Friendly Soap Soap). The approach used in this activity was Participatory Action Research (PAR), which involved five main stages: (1) identifying environmental problems and opportunities for nature-based solutions; (2) collaborative action planning between the implementation team and the school; (3) implementing activities in the form of counseling, presentations, and practicing natural soap making; (4) observing student involvement and understanding; and (5) reflecting on and evaluating the results of the activity. During the implementation, students showed high enthusiasm and active involvement in each session. They not only understood the concept of environmentally friendly products but also developed practical skills in mixing soap from soap nuts, packaging the products, and printing their creations in front of peers and teachers. This activity provided a space for students to learn contextually, collaboratively, and creatively. The final results showed that this activity was effective in improving students' ecological literacy, social skills, and entrepreneurial interests. Thus, this workshop serves as a concrete example of the application of sustainable education that not only equips participants with knowledge but also encourages them to become agents of change in protecting the environment.